Urdu Poetry Archive (2005)
[Dt.:] Eine Sammlung von Urdu-Lyrik, Ghazals und Nazms ausgewählter Dichter. Ein Index mit dem Namen der Autoren und den Titeln der Gedichte erleichtert die Navigation innerhalb der Website. Die Texte der Gedichte sind in lateinischer Transliteration veröfföentlicht. - [Engl.:] A collection of Urdu poetry, ghazals and nazms. The ghazals and nazms in the Urdu poetry archive have been indexed alphabetically as well as by poet. The Index of Singers has been revamped and is now available under Ghazal Singers. This is a relatively new section and covers only a few singers at the moment. The ghazals and nazms are written in transliterated Urdu (Urdu written in the English script)